Antartica's Sovereignty: Adoption of Artic Council Concept as a Better Replacement for Antartica Treaty System (ATS) - Suyatno Ladiqi; Akmal Hamzah (Departemen Hubungan Internasional, Fakultas Ilmu Sosial dan Ilmu Politik, Unair, 2019)
The conflict surrounding the sovereignty over the region of Antarctica is a long-standing issue that has plagued the claimant states for decades. The exhaustion of mineral and raw material fuels the hostility and struggle for dominance over the unclaimed region which beliefs to be the largest remaining reserve of oil and gas as well as other valuable natural resources. With growing number of claimant states and the inexistence of proper international framework, the issue over Antarctica is a time-ticking bomb waiting to burst and causes a major friction over the South Pole. Due to the success achieved by Arctic Council in managing the Arctic region inspire this paper to propose and evaluate the idea of establishing an “Antarctica Council” as a crucial recourse to solve what Antarctica Treaty System (ATS) has failed to achieve. This paper is an examination of analysis and critiques in legal documents and international reports that seek a critical approach over the ineffectiveness of the existing legal framework and possible improvement in Arctic council concept adoptions.